2022
DOI: 10.1177/17470161221094134
|View full text |Cite
|
Sign up to set email alerts
|

Ethical research landscapes in fragile and conflict-affected contexts: understanding the challenges

Abstract: As the prevalence of conflict and fragility continue to rise around the world, research is increasingly heralded as a solution. However, current ethical guidelines for working in areas suffering from institutional and social fragility, insecurity or violent conflict have been heavily critiqued as highly abstract; focussed only on data collection; detached from the realities of academia in the Global South; and potentially extractive. This article seeks to respond to that assessment by spotlighting some of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
(53 reference statements)
3
6
0
Order By: Relevance
“…As with other research from fragile contexts (e.g., Fox et al, 2020;Shanks & Paulson, 2022), the participants in our study noted that some ethical complexities cannot be anticipated.…”
Section: Rq3: What Key Supports Assist Students and Supervisors To Na...supporting
confidence: 60%
“…As with other research from fragile contexts (e.g., Fox et al, 2020;Shanks & Paulson, 2022), the participants in our study noted that some ethical complexities cannot be anticipated.…”
Section: Rq3: What Key Supports Assist Students and Supervisors To Na...supporting
confidence: 60%
“…In many respects GCRF marked a positive shift away from some of the welldocumented historical challenges in South-North research partnerships (Court, 2004;Ishengoma, 2016;Bradley, 2017;Rethinking Research Collaborative, 2018;Grieve and Mitchell, 2020;Asare et al, 2022). Typically, these partnerships are funded by Northern agencies that establish the eligibility criteria in terms of disciplinary or research focus and stipulate the modalities of partnership (Shuayb and Brun, 2021;Shanks and Paulson, 2022). Such research tends to be applied and is often interdisciplinary in nature and focuses on problems physically located in the Global South (Crossley and Holmes, 2001;Bradley, 2017;Tabulawa, 2017).…”
Section: Coloniality and Historical In/equities In International Rese...mentioning
confidence: 99%
“…Funded partnerships often include an explicit 'capacity building' element which regularly reflects a deficit view of Southern capacities and an inflated sense of Northern knowledge and expertise (Koch, 2020;Walker and Martinez-Vargas, 2020;Axelby et al, 2022). Within international research teams there is a tendency for Northern researchers to take the lead in establishing research agendas and assuming intellectual leadership of projects in ways that position Southern researchers as data collectors or junior partners within studies wholly designed in the North (Grieve and Mitchell, 2020;Mkwananzi and Cin, 2021;Shanks and Paulson, 2022). For example, in the field of education a recent study that focused on the equity of collaborative research projects involving African-based researchers found that half of the projects initiated by Northern researchers positioned African partners as implementers of Northern projects rather than genuine collaborators, even in the case of senior academics (Asare et al, 2022).…”
Section: Coloniality and Historical In/equities In International Rese...mentioning
confidence: 99%
See 2 more Smart Citations